Sparticle Masses in a Supersymmetric Grand Unified Model - Hieu, Tran Minh (Communications in Physics, 2011)
In this paper, we investigate the phenomenological aspect relevant to the sparticle masses of a supersymmetric grand unified model, in which the $SU(5)$ is used as the grand unified group with the minimal particle contents and supersymmetry breaking is mediated by the so-called gaugino mediation mechanism. A detailed analysis about the dependence of the squarks and sleptons masses on the free parameter space is given, and shown to be useful for the collider phenomenological study and parameter determination for future experiments.